Synthesis and Crystal Structure Determination of Sodium Molybdate Dihydrate - Capitelli, Francesco; Selim, Md.; K. Mukherjee, Kalyan (Asian Journal of Chemistry, 2010)
The compound sodium molybdate dihydrate (Na2MoO4×2H2O) has been synthesized from aquous medium. Orange single crystal of the compound has been diffracted for structural analysis. The structure of the molecule has been determined with better refinement and the positions of the hydrogens of the H2O molecule have also been located.